Perception of Subject Matter Experts (SMEs) on various curation and preservation techniques for the development of natural history gallery in Malaysia: a qualitative study - Z., Fatin; N., Othman; H., Haris; Najmuddin, M. F.; M. N., Indara Rahayu; Md Zairi, Z.; Abdul-Latiff, M. A. B. (2020)
Preserving animal’s body or part of the animals have become an important and wellknown conservation medium to ensure that the future generations are still able to enjoy the biodiversity and all the incredible species that live within it. This paper aims to present a qualitative study on perception and preference of subject matter experts (SMEs) on various curation and preservation methods that is suitable for certain animals for the development of Natural History Gallery. Interview with the SMEs were done by using semi-structured questionnaire and prior to this, permission were gained from the respondents by signing the Informed Consent Form (ICF). The findings suggest that the preservation methods of specimens ultimately depend on the purpose of specimens collected, either to be preserved as research specimens or exhibition specimens. The information gained form this study will be valuable as directive for the development of natural history gallery in Malaysia.